Immunological Status of Isolated Lymphoid Follicles After Intestinal Transplantation. Issue 9 (1st August 2014) - Meier, D.; Docena, G. H.; Ramisch, D.; Toscanini, U.; Berardi, G.; Gondolesi, G. E.; Rumbo, M.
<x xml:space="preserve">Abstract</x> Intestinal transplantation (ITx) faces the challenge of grafting a high immunogenic organ, which is certainly one of the major obstacles for intestinal allograft acceptance. The allograft has to guarantee the proper functioning of the mucosal immune machinery under immunosuppressive conditions. Recently, it has been elucidated that isolated lymphoid follicles (ILFs) are an indispensable part of mucosal immunity to maintain IgA synthesis and consequently to control commensal microflora. No data about these follicular structures in the setting of ITx are available so far. Therefore, we addressed the question whether constitution, integrity and function of allograft ILFs are disturbed by immunosuppressive regimen. We compared allograft ILFs from terminal ileum of transplant patients with ILFs from nontransplant patients via flow cytometry, quantitative real‐time polymerase chain reaction and immunohistochemistry. We found that host leukocytes rapidly repopulate allograft ILFs and that maintenance immunosuppressive regimen, tacrolimus and corticosteroids, does not affect their cellular integrity and function. However, allograft ILFs revealed a higher maturation state than control samples and IgA positive plasma cells were increased in number in allograft mucosa. Our results open the path for a better understanding of allograft mucosal immunity.